SISTEM INFORMASI AKUNTANSI PERHITUNGAN INSENTIF OPERATOR BERBASIS WEB PADA TERMINAL PETIKEMAS BANJARMASIN PT. PELABUHAN INDONESIA III (PERSERO) REGIONAL KALIMANTAN) - Bahit, Muhammad; Intan, Paraswati; Phaureula Artha, Wulandari (Prosiding Seminar Nasional Manajemen, Ekonomi dan Akuntansi, 2021)
The success of the company is very dependent on quality human resources and is appreciated for their performance by providing operating incentives so that they can increase employee motivation, as a reward for employee attitudes, and the company will more easily achieve its goals if employees always achieve company targets. Therefore, it is necessary to calculate the right operator incentives to avoid mistakes in the process of providing incentives that have an impact on employee performance. This study aims to create a web-based accounting system for calculating employee incentives. The research method used is research and development/ R&D with a case study of Banjarmasin Container Terminal PT. Indonesian Port III (PERSERO) Kalimantan Region. The results of the study can be applied to simplify the process of calculating employee incentives to avoid errors in the input process